Prognostic Significance and Advantage of Echocardiography in The Diagnosis of Ischemic Heart Disease - Boyqo‘ziyeva M.B. (Genius Journals, 2023)
The control group consisted of 20 conditionally healthy patients aged 60 years (49.1 ± 2.98) without clinical manifestations of coronary artery disease and the absence of its main risk factors. Depending on the clinic, the results of the study, the patients were divided into 2 groups. Group I patients consisted of 20 conditionally healthy men aged 37 to 61 years (49.2 ± 2.87) with two risk factors for IHD. Group II included 20 men aged 39 to 64 years (49.5 ± 3.01) with typical bouts of exertional angina. All the examined patients underwent tissue stress-DehoKG technique with physical activity. Physical activity according to the method was used as a stress agent.
Keywords: cardiovascular diseases; ischemic heart disease; dobutamine